The Hound of the Baskervilles - Doyle, Arthur Conan (Delhi : Rohan Book Company, 2004)
A dramatic adaptation with musical accompaniment of Sir Arthur Conan Doyle's famous story. The strange death of Sir Charles Baskerville draws Sherlock Holmes to the gloomy Devon moor, where his courage and astute intellect are severely tested.
Nicol Williamson (Sherlock Holmes), George Rose (Dr. Watson), Caedmon Players, with Gordon Gould.
Keywords: Generational curses